2022
DOI: 10.5694/mja2.51733
|View full text |Cite
|
Sign up to set email alerts
|

A vision of a One Health system for Australia: on the need to rethink our health system

Abstract: Future threats require an integrated approach to the health of humans, animals and the environment Open access: Open access publishing facilitated by The University of Sydney, as part of the Wiley -The University of Sydney agreement via the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These improve coordination and integration of activities and programs across sectors [ 12 ]. The platforms and networks facilitate integrated engagements of multiple disciplines beyond zoonotic diseases such as antimicrobial resistance, food safety, non-communicable diseases, and climate changes [ 114 ]. Our study also found that majority of the publications emphasised the importance of the governance and mentioned the relevant policies that impact the One Health process.…”
Section: Discussionmentioning
confidence: 99%
“…These improve coordination and integration of activities and programs across sectors [ 12 ]. The platforms and networks facilitate integrated engagements of multiple disciplines beyond zoonotic diseases such as antimicrobial resistance, food safety, non-communicable diseases, and climate changes [ 114 ]. Our study also found that majority of the publications emphasised the importance of the governance and mentioned the relevant policies that impact the One Health process.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental health data will continue to be a priority as we see the effects of a changing climate on health outcomes. Australia is considering the development of a national Centre for Disease Control to address emerging and existing health risks and this may address some of the current gaps within the management of zoonoses ( 52 ). However, it is yet to be seen if a One Health approach will be supported and how the management of zoonoses within communities will be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Australia called for Australia to set up its own national centre for disease control, to deliver One Health; the paper stressed the need for integration [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst transmission of avian flu to humans is rare, there is a small chance of mutation to a pandemic strain. A recent editorial in the Medical Journal of Australia called for Australia to set up its own national centre for disease control, to deliver One Health; the paper stressed the need for integration [6][7][8].…”
Section: Introductionmentioning
confidence: 99%